Development of a grooming process for an agile software team in the automotive domain - Ribeiro, Francisca (2018)
At the current unpredictable technical evolution, the market is demanding an increasingly flexibility from companies to adapt to the pace of change in what customers want. The present research was developed in an automotive company, where software teams are pursuing Agile methodologies to coupe with these challenges. Teams use the Scrum framework, however, lack of efficient communication among team members results in poor performance of the product owner and the development team. In an attempt to solve this issue and according to the needs shared by the teams, this paper proposes a grooming process for a Scrum team. It provides a step-wise approach to work breakdown, from customer requirements elicitation to the development of ready work entities using the user story format. This paper describes how agile methods can support requirements engineering in a software project.